Implementasi Prinsip Good Governance Pada Kantor UPTD Samsat Manado - Finelin Tahulending; Sisca Beatrix Kairupan; Devie Siwij; M Rivandy S (Post Graduate School of Government Science, 2023)
Good Governance is a very important factor in public services, as well as a gateway to achieving a predetermined goal. The method to be used in this study is a qualitative research method. In this study, the researchers focused more on the implementation of the principles of effectiveness and efficiency as well as the principles of justice for good governance and the factors that hindered the implementation of the principles of good governance at the UPTD Samsat Manado office. The results of the research implementation of the principles of good governance regarding indicators of effectiveness and efficiency have been implemented in the Manado Samsat Joint Office, where employees are disciplined in carrying out their responsibilities, and employees are able to carry out the vision and mission that have been set at the Manado Samsat Joint Office, Employees at the Manado Samsat Office as well able to provide easy service. So that the services provided by the Manado Samsat Joint Office can prosper the tax payer community. The implementation of the principles of good governance with indicators of justice in public services is explained that the principle of justice in providing services at the Manado Samsat Joint Office has not been said to be fair because it still uses a family or insider system. . So that some taxpayers feel unfairness in service at the Manado Samsat Joint Office.